e-Powered Multi-purpose two-row seeder for smallholders - SINGH, S P; SINGH, MUKESH K; EKKA, UTPAL; SINGH, M K (The Indian Journal of Agricultural Sciences, 2019)
Spinach and coriander are cultivated using traditional method by majority of marginal and small landholders. No seed drill is available for sowing of these vegetable crops. The objective of present study was to provide such a seeder that can reduce manual work done by farmers. An attempt was made to develop electric power (e-power) walk behind seeder at ICAR-IARI, New Delhi in year 2015. The major workload was shared by e-power. The unit consisted of a DC geared motor, batteries, power transmission unit, independent seeding units with vertical cell fed metering mechanism, swinging handle and frame. The seeder was tested for spinach, coriander and wheat seeds. Lab study on sticky belt indicated that wheat seed showed better uniformity in distribution followed by spinach and coriander. From field studies, output with e-powered 350W seeder was 1130 m2/h at a speed of about 2.9 km/h with field efficiency of 90.3% for tested seeds. The average draft requirement of machine was 106.1N. The developed equipment provided 2.5 times more output than manually operated seed drill with reduced drudgery by 2.6 times in terms of muscular force requirement.